Offences and prejducies toward kosovar women politician in media - Sylejmani Nimani, Arbenita (Technium Social Sciences Journal, 2021)
Offensive and sexist statements against women politicians in Kosovo and women in general are no longer unknown, especially when they are made public, either through various media or through statuses on various social networks. But, in Kosovo, recently there have been insults against Kosovar women politicians by their colleagues, Kosovar men politicians, which insults clearly tend to increase. These statements contain the following epithets: dealing with their body weight, calling them 'cows', 'beautiful', 'prostitutes', and even inviting them on a date. Also, in the media several times and recently, bias has been noted regarding women’s jealousy by calling them jealous, even of those fighting for human rights. In this paper, content analysis is used, where the contents of some media are analyzed, such as television and some online media. The contents of the messages written against the Kosovar woman politician were analyzed. Offensive statements and prejudices against Kosovar women politicians were pointed out to be very harmful, because this could damage the chances of women politicians to be successful and could contribute to the woman being further qualified only on the basis of her beauty and not to be treated according to its wisdom.